Floral biology and breeding system of endangered species: Parmentiera cereifera Seem. (Bignoniaceae) - Janis Damaiyani (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2021)
Parmentiera cereifera Seem. is an endangered species in the family Bignoniaceae. Related to the conservation effort, information about the reproductive biology of this species is very limited. Based on that, the objectives of this study were to provide knowledge about the reproductive properties such as floral biology and breeding system of P. cereifera. The research was conducted at Purwodadi Botanic Garden, from October 2019 to February 2021. Several important aspects of reproductive biology, including flower biology, pollen viability and stigma receptivity, pollen morphology and breeding system were investigated. The viability was tested with TTC (2, 3, 5–triphenly tetrazolium chloride) and stigma reseptivity was tested with hydrogen peroxide. The breeding system was determined based on outcrossing index (OCI) using Cruden's method. The results showed that P. cereifera flower was monoecious, had morphological character that supported nocturnal pollination. Stigma and anthers spatially separated, but there was no temporal separation of stigma receptivity and anther dehiscence. Based on the flower biology, the pollen ornamentation (reticulate type), and the Out-Crossing Index (OCI=4), the breeding system was outcrossing but partially self-compatible, required pollinators (zoophily)